Citizenship allocation and withdrawal: Some normative issues. Issue 12 (10th October 2017) - Ferracioli, Luara
Abstract: Philosophical discussion about citizenship has traditionally focused on the questions of what citizenship is, its relationship to civic virtue and political participation, and whether or not it can be meaningfully exercised at the supra‐national level. In recent years, however, philosophers have turned their attention to the legal status attached to citizenship and have questioned existing principles of citizenship allocation and withdrawal. With regard to the question of who is morally entitled to citizenship, philosophers have argued for principles of citizenship allocation that go beyond birth and lineage and have focused instead on the value of political attachment and located life plans. These principles have several advantages over existing legal principles, but they suffer from being under‐specified, as well as being over and under‐inclusive. With regard to loss of citizenship, philosophers have primarily denounced citizenship withdrawal as a form of punishment by appealing to principles of fair and equal treatment. However, theories purporting to show that denationalization is always wrong have trouble explaining why loss of citizenship is so problematic for persons who have committed the most horrendous crimes against their fellow citizens and who, in so doing, have in effect self‐excluded from the political community.